The Effect of Ratio of Yam and Tamarind Juices and the Type of Stabilizer on the Quality of Tamarind Syrup - Fitri Utami; Zulkifli Lubis; Linda Masniary Lubis (Jurnal Rekayasa Pangan dan Pertanian, 2016)
The aim of this research was to determine the effect of ratio of yam  and tamarind juices and the type of stabilizer on the quality of tamarind syrup. This research was using factorial Completely Randomized Design (CRD) with two factors, i.e : ratio of yam and tamarind juices  (S)   ( 30:70%, 40:60%, 50:50%, 60:40%, 70:30%) and type of stabilizer (xanthan gum, arabic gum, and guar gum). The analyzed parameters were vitamin C content, total soluble solid, total acid, pH, viscosity, and organoleptic values (colour, aroma, and taste). The results showed that the ratio yam  and tamarind juices had highly significant effect on vitamin C content, total soluble solid, total acid, pH, viscosity, and organoleptic values (colour, aroma, and taste). Type of stabilizer had highly significant effect on viscosity and organoleptic values of taste. The interaction of the two factors had highly significant effect on organoleptic values of taste. The best treatment which gave the best effect on the juice was 30:70% of yam and tamarind juices and xanthan gum. Keyword :   ,  arabic  gum,  guar gum,  stabilizers, tamarind , xanthan gum, yam